2010
DOI: 10.1152/jn.00754.2009
|View full text |Cite
|
Sign up to set email alerts
|

Irritancy Expectancy Alters Odor Perception: Evidence From Olfactory Event-Related Potential Research

Abstract: Bulsing PJ, Smeets MAM, Gemeinhardt C, Laverman M, Schuster B, Van den Hout MA, Hummel T. Irritancy expectancy alters odor perception: evidence from olfactory event-related potential research. J Neurophysiol 104: 2749 -2756, 2010. First published September 15, 2010 doi:10.1152/jn.00754.2009. The aim of the present research was to investigate the influences of cognition on temporal processing of olfactory information in a health-relevant context. We investigated whether expecting an odor to cause adverse healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…In conclusion, by manipulating the verbal context, we showed that recovery of neural olfactory representation depends on the available lexical information. These findings are in line with a large set of data suggesting that contextual and verbal information present during odor encoding is a prominent factor in the emergence of olfactory representations [Ayabe‐Kanamura et al, ; Bensafi et al, ; Bulsing et al, ; Dalton, ; de Araujo et al, ; Distel and Hudson, ; Djordjevic et al, ; Moskowitz, ; Poncelet et al, b]. Odors are generally emitted by a food, flower, place, animal, perfume, cosmetic, or person, and it is of this context that we are aware concurrently with the smell.…”
Section: Discussionsupporting
confidence: 79%
“…In conclusion, by manipulating the verbal context, we showed that recovery of neural olfactory representation depends on the available lexical information. These findings are in line with a large set of data suggesting that contextual and verbal information present during odor encoding is a prominent factor in the emergence of olfactory representations [Ayabe‐Kanamura et al, ; Bensafi et al, ; Bulsing et al, ; Dalton, ; de Araujo et al, ; Distel and Hudson, ; Djordjevic et al, ; Moskowitz, ; Poncelet et al, b]. Odors are generally emitted by a food, flower, place, animal, perfume, cosmetic, or person, and it is of this context that we are aware concurrently with the smell.…”
Section: Discussionsupporting
confidence: 79%
“…This phenomenon is mainly interpreted as modality-specific tuning of the sensory cortex as a result of conditioning, which allows enhanced encoding of the emotionally and motivationally significant stimulus (Weinberger, 2004). Consistent with this, recent studies on chemosensory event-related potentials (ERP) have shown a modulation of ERP components as early as the N1 by pain expectancy, supporting an effect of salience on the very first sensory processing levels (Bulsing et al, 2007, 2010). In our study, the differential response was more pronounced in the right POC, which might result from the right-sided olfactory stimulation and subsequent ipsilateral projections into the POC (Gottfried, 2006).…”
Section: Resultssupporting
confidence: 54%
“…‘therapeutic’) [35] and [36]. More surprisingly, however, we also found that this same odorant characterization significantly and persistently increased airway inflammation among individuals who were led to believe that it could induce asthma symptoms.…”
Section: Discussionmentioning
confidence: 55%